Response Surface Methodology: Optimisation of Antifungal Bioemulsifier from Novel Bacillus thuringiensis - Deepak Rajendran; Ponnusami Venkatachalam; Jayapradha Ramakrishnan (The Scientific World Journal)
An antifungal bioemulsifier compound was produced from a novel strain of Bacillus thuringiensis pak2310. To accentuate the production and as the first step to improve the yield, a central composite design (CCD) was used to study the effect of various factors like minimal salts (1X and 3X), glycerol concentration (2% and 4%), beef extract concentration (1% and 3%), and sunflower oil concentration (2% and 4%) on the production of bioemulsifier molecule and to optimize the conditions to increase the production. The E24 emulsification index was used as the response variable as the increase in surfactant production was seen to be proportional to increased emulsification. A quadratic equation was employed to express the response variable in terms of the independent variables. Statistical tools like student’s t-test, F-test, and ANOVA were employed to identify the important factors and to test the adequacy of the model. Under optimum conditions (1X concentration of minimal salts (MS), 2.6% glycerol (v/v), 1% beef extract (w/v), and 2% sunflower oil (v/v)) a 65% increase in yield was produced.